Pedometers and participatory schoolbased health education - an exploratory study. Issue 6 (20th August 2014) - Bruselius-Jensen, Maria Louisa; Danielsen, Dina; Hansen, Ane Kirstine Viller
Abstract : Purpose: The paper explores how pedometers (a simple gadget that counts steps) can be used as a tool in participatory health education to enhance primary school chil-dren's insights into and abilities to reflect on physical activity in their daily life. The paper focuses on how the use of pedometers brings about participation, and enhances reflection on physical activity. Design/methodology/approach: The paper draws on findings from an exploratory project with 6th grade classes (12-13 years) in four Danish primary schools. The approach is called Imove. In Imove pupils use pedometers to study their own patterns of physical activity, transform their data into statistics and use the statistic representation to reflect on how physical activity is integrated into everyday life patterns, and how different activities constitute an active life. Findings: The paper concludes that pedometers support pupils' participation in the study of their own health practices and the step data provide new insights and encourage pupils to reflect on how physical activity forms into everyday patterns. Research limitations/implications: The study is an exploratory study with four participating school classes. The find-ings need to be further explored in larger studies. However, it strongly indicates that pedometers support the genuine participation of pupils in health educational processes. Practical implications: The findings identify simple measuring technologies such as pedometers as potent assets in health educational learning processes and call for creative thinking in the development of health promotion programs for young people. Originality/value: Measuring technologies play an increasing role in health research, as well as in in-dividual health regulating practices. This paper contributes with a new perspective by demonstrating the educative possibilities of applying pedometers in participa-tory school health education.